STRATEGI PEMERINTAH DAERAH DALAM PENGEMBANGAN OBJEK WISATA 2012-2013 (studi kasus objek wisata Gelombang Bono Teluk Meranti) - Tri Wahyuni; Raja Muhammad Amin (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
Bono attractions located in the district of Teluk Meranti Located in kampar peninsula Pelalawan. For businesses that need to be planned and serious develoment of government and agencies Pelalawan BUDPAPORA Pelalawan. Sucessful development of tourism potetial is determined by the maturity and seriousness of the government in carrying out duties and fuctions.Reseacrh by the author will eventually reveal the constraints of attraction development process Bono performed by BUPAPORA service that has been running but not much progress in providing attractions Bono who was appointed as an icon Pelalawan. Can in saying that the development of tourism attaractions Bono has not be realized well with barries to lack of coordination with other agencies BUDPAPORA office and the public has not been aware of Teluk Meranti. so much tourist needs to support local governments to promote anda create an attraction that is nautical and tourist concious society.Keyword : attraction Bono, regional Touism, development